Reduced common carotid artery longitudinal wall motion and intramural shear strain in individuals with elevated cardiovascular disease risk using speckle tracking. (16th July 2015) - Tat, Jimmy; Au, Jason S.; Keir, Peter J.; MacDonald, Maureen J.
Summary: Longitudinal motion of the intima–media and adventitia layers of the common carotid artery (CCA) wall were assessed with ultrasound speckle tracking in seven individuals with spinal cord injury (SCI), who are considered at increased risk of cardiovascular disease, and in seven able‐bodied participants. CCA longitudinal wall displacement and intramural shear strain were compared to traditional markers of arterial health, including CCA stiffness and intima–media thickness (IMT). For each cardiac cycle, longitudinal CCA wall motion was characterized by bidirectional movement patterns containing motion retrograde to blood flow during systole, followed by antegrade motion during diastole. Relative displacement of the intima–media versus the adventitia was used to calculate longitudinal intramural shear strain and provided insight to local arterial wall properties. The retrograde intramural shear strain was smaller in individuals with SCI by 60·2% ( P <0·05) compared to able‐bodied participants, showing smaller peak displacements in both the intima–media ( P <0·05) and adventitia ( P <0·05). In the antegrade direction, there were no group differences in either longitudinal displacements or shear strain. The group differences observed in the retrograde wall motion phase were greater than those observed for CCA stiffness or IMT and were found to be independent of both indices, indicating indices of the retrograde phase intramural shear strain may be a novel and sensitive marker of vascular health. Our findings demonstrate that assessment of longitudinal arterial wall shear strain may provide valuable insight into vascular structure and function and may hold potential for the early detection of cardiovascular disease.